Reservoir and rock characterization for Mishrif Formation/ Zubair Field (Rafdiya and Safwan Domes) by nuclear magnetic resonance and cores analysis - N. Al-Dujaili, Ahmed (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
The identification studies of rock and reservoir characteristics are essential for evaluating the efficiency of a reservoir by analyzing the types of rock and pores. In this study, Nuclear Magnetic Resonance (NMR) for six wells was utilized to identify the rock and reservoir characteristics of the Mishrif formation in the South of the Zubair Field, specifically the Rafdyia and Safwan domes, as well as the west flank. Specific correlations were utilized to describe the classification of rocks, estimate pore throat radius, and recognize possible flow intervals. The results revealed that the Mishrif Formation mainly consists of limestone, dolomite, and shale. The Safwan dome consists mainly of pack-wackestone, wackestone, and mudstone, while the Rafdyia dome is a mixture of packstone, grainstone, and wackestone with some shoal and rudist bioherm facies. The west flank is characterized by pack-wackestone, wackestone, and mudstone. These results were further supported by core analysis. Pore throat types in the Safwan dome range from Micropores to Nanopores, while the Rafdyia dome is dominated by Megapores, Macropores, and Mesopores. The back-shoal facies overwhelm the packstone microfacies. The west flank of the Mishrif Formation in the Zubair Field is mesoporous and micropores. Flow units were identified in the Safwan and Rafdyia domes, as well as the west flank. The Safwan dome has fifteen flow units in the north and seven in the south, while the Rafdyia dome has ten flow units in both the north and south regions, with five flow units on the west flank of the Zubair Field.